Recent Progress in Electromagnetic Production of Associated Strangeness on the Nucleon - Terry Mart (Jurnal Matematika & Sains, 2007)
We discuss recent developments in electromagnetic production of kaon of a nucleon. A detailed chronological progress in this field is presented. Special attention is given for the isobar model which is not only useful for explaining experimental data, but also important in the nuclear application. Other applications, such as in the quest of "missing resonances" and in the investigation of the hadronic as well as electromagnetic baryon form factors, are also discussed. We also touch on the latest achievements in Regge models and multipole analyses of this process. The basic formalism required for numerical calculations is also thoroughly presented.